2020
DOI: 10.1007/s42729-020-00188-z
|View full text |Cite|
|
Sign up to set email alerts
|

Vermiculite-Lizardite Industrial Wastes Promote Plant Growth in a Peat Soil Affected by a Cu/Ni Smelter: a Case Study at the Kola Peninsula, Russia

Abstract: Some industrial barren areas are extreme habitats created by the deposition of airborne pollutants from non-ferrous smelters. One of such barrens exists in the vicinities of the Cu/Ni smelter, located at the Kola Peninsula, Murmansk region, Russia. This study aimed at evaluating in laboratory conditions the efficiency of various vermiculite-lizardite wastes (industrial wastes of local origin) as soil amendments for plant growth promotion. Peat topsoil (0-20 cm) was collected in the vicinity of the Cu/Ni smelte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
3
6
0
1
Order By: Relevance
“…Consistent with this finding, our recent experiment under laboratory conditions were similar to those in the present study (Tarasova et al, 2020), demonstrating a linear relationship between L. perenne shoot length and growth time in uncontaminated commercial peat. In contrast, Tarasova et al (2020) revealed a non-linear relationship of shoot growth with growth time in polluted Histosol extracted from the vicinity of the Ni/Cu smelter, both before and after treatment. Given that the study of Tarasova et al (2020) used substrates of peats diffe- ring only in the degree of metal pollution, we infer that plant growth was negatively impacted by metal toxicity in polluted soils even after treatment.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with this finding, our recent experiment under laboratory conditions were similar to those in the present study (Tarasova et al, 2020), demonstrating a linear relationship between L. perenne shoot length and growth time in uncontaminated commercial peat. In contrast, Tarasova et al (2020) revealed a non-linear relationship of shoot growth with growth time in polluted Histosol extracted from the vicinity of the Ni/Cu smelter, both before and after treatment. Given that the study of Tarasova et al (2020) used substrates of peats diffe- ring only in the degree of metal pollution, we infer that plant growth was negatively impacted by metal toxicity in polluted soils even after treatment.…”
Section: Resultssupporting
confidence: 92%
“…We noted that early shoot growth in grasses-and Lolium species in particular-had a linear relationship with growth time (Thomas et al, 1999). Consistent with this finding, our recent experiment under laboratory conditions were similar to those in the present study (Tarasova et al, 2020), demonstrating a linear relationship between L. perenne shoot length and growth time in uncontaminated commercial peat. In contrast, Tarasova et al (2020) revealed a non-linear relationship of shoot growth with growth time in polluted Histosol extracted from the vicinity of the Ni/Cu smelter, both before and after treatment.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations